A small‐gain approach to networked control systems with asynchronous communication. Issue 1 (October 2016) - Geiselhart, R.; Borgers, D.P.; Heemels, W.P.M.H.
Abstract: The aim of this work is to give a procedure to compute an ISS Lyapunov function (ISS ‐ input‐to‐state stability ) for a large‐scale networked control system (NCS) in which sensors, controllers and actuators are connected via multiple communication networks that operate asynchronously, [1]. The main idea is that the NCS is modeled as an interconnection of controlled subsystems and (hybrid) error systems, for which local ISS Lyapunov functions can be derived from the underlying medium access control (MAC) protocol systematically. The application of a small‐gain result leads to the construction of an ISS Lyapunov function for the whole NCS. In particularly, maximally allowable transfer intervals (MATIs) and maximally allowable delays (MADs) for each communication network can be computed that are directly related to the ISS gains and convergence rates. In this respect, tradeoffs between the quality‐of‐control (QoC) of the whole NCS and the quality‐of‐service (QoS) of the communication networks become explicit. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)